Air pollution control efficacy and health impacts: A global observational study from 2000 to 2016. (15th October 2021) - Han, Chunlei; Xu, Rongbin; Zhang, Yajuan; Yu, Wenhua; Zhang, Zhongwen; Morawska, Lidia; Heyworth, Jane; Jalaludin, Bin; Morgan, Geoffrey; Marks, Guy; Abramson, Michael; Sun, Liwei; et al.
Abstract: Particulate matter with aerodynamic diameter ≤2.5 μm (PM2.5 ) concentrations vary between countries with similar carbon dioxide (CO2 ) emissions, which can be partially explained by differences in air pollution control efficacy. However, no indicator of air pollution control efficacy has yet been developed. We aimed to develop such an indicator, and to evaluate its global and temporal distribution and its association with country-level health metrics. A novel indicator, ambient population-weighted average PM2.5 concentration per unit per capita CO2 emission ( P M 2.5 / C O 2 ), was developed to assess country-specific air pollution control efficacy (abbreviated as APCI). We estimated and mapped the global average distribution of APCI and its changes during 2000–2016 across 196 countries. Pearson correlation coefficients and Generalized Additive Mixed Model (GAMM) were used to evaluate the relationship between APCI and health metrics. APCI varied by country with an inverse association with economic development. APCI showed an almost stable trend globally from 2000 to 2016, with the low-income groups increased and several countries (China, India, Bangladesh) decreased. The Pearson correlation coefficients between APCI and life expectancy at birth (LE), infant-mortality rate (IMR), under-five year of age mortality rate (U5MR) and logarithm of per capita GDP (LPGDP) were −0.57, 0.65, 0.66, −0.59 respectively (all P values < 0.001). APCI could explain international variation of LE, IMR and U5MR. The associations between APCI and LE, IMR, U5MR were independent of per capita GDP and climatic factors. We consider APCI to be a good indicator for air pollution control efficacy given its relation to important population health indicators. Our findings provide a new metric to interpret health inequity across the globe from the point of climate change and air pollution control efficacy. Graphical abstract: Image 1 Highlights: PM2.5 /CO2 is a useful indicator of air pollution control efficacy. Developed countries have higher air pollution control efficacy. Air pollution control efficacy is a good predictor for population health. Global air pollution control efficacy changed minimally during 2000–2016. Air pollution control efficacy decreased in China, India, and Bangladesh.